Conditions and Criteria for Sustainable Development of the Financial System - ISKAKOVA, Zagira; KUPALOVA, Galina; SRAILOVA, Gulnara; AMERKHANOVA, Altyn; ISCHANOVA, Ruslana (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
Strategic management of the financial system of the Republic of Kazakhstan in the context of the globalization of the economy is one of the main conditions and factors for ensuring financial stability in the country. The implementation of supervisory powers in the financial sphere is carried out in each country in the institutional forms established by law. The choice of a specific method of regulating organization is determined by the set of factors characteristic for each country. The forms of implementation of regulatory functions in each particular country do not remain unchanged, they are constantly being improved. The creation of a separate regulatory body to oversee all participants of the financial market in the Republic of Kazakhstan is an important step in the development of the regulation of the financial system of the Republic of Kazakhstan. World practice shows that such a regulatory framework is most effective for the development of the financial sector, financial instruments and financial intermediation services. The banking activities of insurance companies, pension funds and other financial institutions are subject to regulation by the state and must comply with the requirements of the law, which contributes to the stability of the financial system. Some insolvency or imperfection of management of the financial system, insecurity from external and internal risks were shown by financial institutions of the state in the conditions of the world economic and financial crisis. The crisis showed that the existing system of managing the financial system of states around the world needs to be improved.